2021
DOI: 10.3389/fmars.2021.669374
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impacts on Beaches and Coastal Water Pollution at Selected Sites in Ecuador, and Management Proposals Post-pandemic

Abstract: The COVID-19 pandemic has obliged Governments all around the world to implement confinement and social distancing measures. Leisure and business activities on beaches and in ports have restricted direct and indirect contamination from, for example, plastics, hydrocarbon spillage, microbiological loads, and noise levels. This has led to temporarily improved environmental conditions, and the beaches having conditions closer to Marine Protected Areas. Here we report some impacts that have been studied using local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…A study in the Venice Lagoon (Italy) found a 50% reduction in total suspended matter (TSM) after lockdown through Very-High Resolution (VHR) PlanetScope Imagery ( Table 1 ) ( Mousazadeh et al, 2021 ; Niroumand-Jadidi et al, 2020 ). Since the reduction of tourists, water quality along beaches in Acapulco (Mexico), Barcelona (Spain), and Salinas (Ecuador) improved noticeably ( Ormaza-Gonzaìlez et al, 2021 ; Zambrano-Monserrate et al, 2020 ). Wagh found a significant reduction in lake water pollution due to lockdown in Lake Hussain Sagar (India) by using two techniques: spectral reflectance and chromaticity analysis ( Wagh et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study in the Venice Lagoon (Italy) found a 50% reduction in total suspended matter (TSM) after lockdown through Very-High Resolution (VHR) PlanetScope Imagery ( Table 1 ) ( Mousazadeh et al, 2021 ; Niroumand-Jadidi et al, 2020 ). Since the reduction of tourists, water quality along beaches in Acapulco (Mexico), Barcelona (Spain), and Salinas (Ecuador) improved noticeably ( Ormaza-Gonzaìlez et al, 2021 ; Zambrano-Monserrate et al, 2020 ). Wagh found a significant reduction in lake water pollution due to lockdown in Lake Hussain Sagar (India) by using two techniques: spectral reflectance and chromaticity analysis ( Wagh et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…As previously mentioned, the restrictions to human movement and social distancing established worldwide, in an attempt to combat the COVID-19 pandemic, impacted the tourism sector, with beach tourism being one of the most affected sectors. The absence of tourists on beaches resulted in notable changes to these ecosystems as described by many researchers (Zambrano-Monserrate et al, 2020 ; Zielinski & Botero, 2020 ; Ormaza-González et al, 2021 ; Edward et al, 2021 ; Loizia et al, 2021 ). According to Mousazadeh et al ( 2021 ), tourist restriction on beaches has resulted in the evident reduction of pollutants in the water and as a consequence, many animals have returned to these habitats.…”
Section: Discussionmentioning
confidence: 95%
“…Tourism activities during the COVID- 19 pandemic were strongly affected globally, experiencing a global reduction of approximately 73% and an estimated economic loss of almost 2 trillion dollars in 2020 compared with 2019 pre-pandemic year (UNWTO, 2021 ). As such, coastal tourism was one of the most affected sectors (Ormaza-González et al, 2021 ). Social distancing and lockdowns imposed by many countries considerably reduced the level of anthropic pressure on environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global water pollution also declined, likely due to the decrease in industrial and agricultural activities as reported in heavily populated countries like China ( Shen et al, 2021 ), India ( Singh & Mishra, 2021 ), and Pakistan ( Shafeeque et al, 2021 ). Globally, the period of COVID-19 restrictions also provided relief (reducing litter, and plastic pollution) to various water bodies, including the coastal areas of Ecuador ( Ormaza-Gonzaìlez et al, 2021 ), Damodar River ( Chakraborty et al, 2021 ), and Vembanad Lake, India (longest lake in India) ( Yunus et al, 2020 ), Kenyan recreational beaches ( Shafeeque et al, 2021 ), and the west coast of Tangier, Morocco ( Cherif et al, 2020 ). Thus, as outlined above and showcased in recent research, many positive environmental impacts were recorded during the initial phase of strict government regulations.…”
Section: Short-term Positive Impacts Of Covid-19 On the Environmentmentioning
confidence: 99%